2011
DOI: 10.1016/j.bone.2011.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Lathyrism-induced alterations in collagen cross-links influence the mechanical properties of bone material without affecting the mineral

Abstract: In the present study a rat animal model of lathyrism was employed to decipher whether anatomically confined alterations in collagen cross-links are sufficient to influence the mechanical properties of whole bone.Animal experiments were performed under an ethics committee approved protocol. Sixty-four female (47 day old) rats of equivalent weights were divided into four groups (16 per group): Controls were fed a semi-synthetic diet containing 0.6% calcium and 0.6% phosphorus for 2 or 4 weeks and β-APN treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 62 publications
3
108
0
Order By: Relevance
“…(38,57) It has recently been shown in animals that alterations in collagen cross-links (most notably the pyr/divalent cross-link ratio), coupled with changes in microarchitecture, are sufficient to adversely affect bone biomechanical performance in the absence of any concomitant changes in mineral quantity and quality, even when these changes are anatomically confined to bone-forming surfaces. (61) Both shorter-term and longer-term RIS use resulted in significantly lower pyr/divalent collagen cross-link ratios compared to ALN, in agreement with a recent publication. (62) It is also in general agreement with previously published reports showing that although RIS administration in postmenopausal women lowered this bone quality index compared to placebo, ALN did not.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(38,57) It has recently been shown in animals that alterations in collagen cross-links (most notably the pyr/divalent cross-link ratio), coupled with changes in microarchitecture, are sufficient to adversely affect bone biomechanical performance in the absence of any concomitant changes in mineral quantity and quality, even when these changes are anatomically confined to bone-forming surfaces. (61) Both shorter-term and longer-term RIS use resulted in significantly lower pyr/divalent collagen cross-link ratios compared to ALN, in agreement with a recent publication. (62) It is also in general agreement with previously published reports showing that although RIS administration in postmenopausal women lowered this bone quality index compared to placebo, ALN did not.…”
Section: Discussionsupporting
confidence: 89%
“…Although these differences may be anatomically restricted to bone-forming surfaces, recent data from animals indicated that such changes are still sufficient to influence bone strength even with no change in the amount and quality of mineral. (61) A limitation of the present study is that end-point biopsies were collected from the patients in the general population, thus compliance with therapy is uncertain. Another limitation is the low sample number of biopsies from patients on RIS for >5 years compared to the other groups.…”
Section: Discussionmentioning
confidence: 95%
“…Although the specific mechanisms responsible are not clear, changes in crystallinity because of BAPN treatment is an interesting finding that warrants further investigation using more direct methods of evaluating changes to the crystalline structure. 27 Another study demonstrated no effects on crystallinity/maturity with BAPN treatment, 13 but these conflicting data may be due to differences in dose (B780 vs 300 mg kg À 1 ), method of delivery (dietary vs subcutaneous injection), animal model (rat vs mouse) and anatomical site (vertebral crosssection vs native surface of femur).…”
Section: Discussionmentioning
confidence: 99%
“…9 The sweet pea (Lathyrus odoratus) contains b-aminopropionitrile (BAPN), 10 which irreversibly binds to the LOX active site, 11 and is a commonly used lathyrogen to experimentally replicate osteolathyrism. [12][13][14][15] Understanding the implications of reduced enzymatic crosslinking is important because crosslinks are reduced with aging and other diseases such as diabetes and osteoporosis. 16 Therefore, treatment with BAPN can serve as a model of osteolathyrism and further our understanding of how nanoscale changes in collagen impact bone strength and fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same animal model, it was recently reported that beta aminoproprionitrile treatment induced a decrease in divalent and trivalent crosslinks, which was associated with a decrease of trabecular thickness and compressive energy to failure, while stiffness was not affected. 32 Another rat study showed that increased homocysteinemia induced by a diet enriched in methiononine or homocysteine -which is likely to interfere with crosslink formation -for 3 months resulted in decreased bone formation, bone volume and bone strength at the distal femur. 33 The impact of an increase of enzymatic crosslinks on bone strength can also be investigated using fetal bovine cortical bone, which is characterized by a low level of these molecules.…”
Section: Collagen Post-translational Modifications and Bone Strengthmentioning
confidence: 99%